Nonlinear Dynamics — 2013 - (:unkn) unknown (National Technical University "Kharkov Polytechnic Institute", 2013)
The book of Proceedings includes extended abstracts of presentations on the Fourth International conference on nonlinear dynamics.
Нелінійна динаміка — 2013
Keywords: Dynamics of Discrete Systems; Dynamics of Distributed Systems; конференції НТУ "ХПІ"; праці вчених НТУ "ХПІ"; конференція з нелінійної динаміки; нелінійна динаміка